(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Sensitivity study of Cnestis ferruginea pulp extract with respect to the reference commercial antibiotics was tested against four bacteria (Staphylococcus aureus, Bacillus subtilis, Proteus mirabilis, and Klebsiella pneumoniae) and three fungi (Trichoderum rubrum, Aspergillus niger, and Candida albicans) strains isolated in man with a view to elucidating the inhibitory potency of the plant pulp’ extract using an agar well diffusion assay. The investigation discovered that the extract had 71% inhibitory activities against the microbial isolates tested either in sterilized or non-sterilized form and in the two different concentrations examined, which compared favourably with reference antibiotics used. The optimal performance of the pulp extract against the test organisms could be due to the presence of the metabolites such as alkaloids, flavonoids, steroids, saponins, and polyphenols found in ample form in the extract. This study has revealed the possible utilization of Cnestis ferrugineain the treatment of wound, urinary infections and in the management of oral-related infections.